Una lectura postpornográfica de Roberto Bolaño: escritura, feminismo y postcolonialismo - Rodríguez, Josué Hernández (Moderna språk, 2021)
The proliferation of critical and creative post-porn movements, which vindicate the representation of dissident sexualities under a new feminist, queer and transgender perspective, provide tools of analysis to rethink past literary and audiovisual pornographic productions, as well as to reformulate current ones. In this line of intermediate research, between cinema and literature, an approach to the work of Chilean writer Roberto Bolaño is proposed that will allow us to discern whether he can be considered a post-porn author related to the Golden Age of pornographic cinema in the 1970s and 1980s. Two of his stories and a novel will be studied: “Joanna Silvestri”, from which a gender reading will be made that problematizes the role of women within an eminently heteronormative industry, obsessed with representing male ejaculation; “Prefiguración de Lalo Cura”, analyzed under a postcolonial perspective of appropriation of subaltern bodies conceived as geographical territories, and Una novelita lumpen, in the field of porn pedagogy. The resulting findings make it possible to establish that Roberto Bolaño can indeed be considered a post-porn author by translating the narrative proposals of the Golden Age porn films into his own literary project, with a feminist and post-colonial critical intention.
Keywords: 2-Approches sociologiques; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir)